THE APPLICATION OF ARTICLE 22 OF THE REGULATION OF THE HEAD OF THE INDONESIAN NATIONAL POLICE FORCE NUMBER 14 OF 2011 CONCERNING THE CODE OF ETHICS OF THE INDONESIAN NATIONAL POLICE PROFESSION - Puhi, Oyaldi; Moonti, Roy Marthen; Kadir , Yusrianto; Pakaya, Salahudin (IBLAM LAW REVIEW, 2023)
The purpose of this study is to determine and analyze the effectiveness of the application of Article 22 of the Regulation of the Chief of the Indonesian National Police Number 14 of 2011 concerning the Code of Professional Ethics of the Indonesian National Police in the Gorontalo Regional Police and to determine and analyze what factors affect the effectiveness of the application of Article 22 of the Regulation of the Chief of the Indonesian National Police Number 14 of 2011 concerning the Code of Professional Ethics of the Indonesian National Police in the Gorontalo Regional Police. The research used is empirical research. Empirical legal research is conducted by examining directly into the field to see directly the application of legislation or rules of law relating to law enforcement, as well as conducting interviews with several respondents who are considered to be able to provide information regarding the implementation of law enforcement. The application of the Regulation of the Chief of the Indonesian National Police (Perkap) is not yet effective, because from the results of the interview that the Gorontalo Regional Police prioritizes the Circular Letter (SE) rather than the Regulation of the Chief of the Indonesian National Police (Perkap), moreover that the debate regarding the application of legal norms does not only occur among law enforcers in general but within the internal police also becomes a debate caused by the existence of conflicting legal norms between high legal norms and low legal norms. Factors affecting the effectiveness of the application of the article on the Regulation of the Chief of the Indonesian National Police regarding the Police Professional Code of Ethics within the scope of the Gorontalo Regional Police, which is the formulation of the problem in this study, including; 1) Legal Substance, 2) Legal Structure, 3) Legal Culture.